The Sub-Saharan Refugee Crisis: Three Decades of Somali Refugees in Kenya, How did Kenya become the home of half a million Somali refugees? - Isobel Rose Meharg (Andalas Institute of International Studies, 2023)
The case study seeks to unpack the origins of Somali displacement and the subsequent Kenyan policy responses to the unfolding crisis. The Somali refugee crisis is unique. Somalia has been the site of one of the longest humanitarian crises in the world. There is not simply one reason for so many globally and internally displaced Somalis, but an accumulation of factors. The research paper shall follow a threefold structure. Firstly, an outline of the context under which these people became refugees to aid understanding of the displacement from Somalia over three decades. Secondly, this paper shall address why Kenya is the predominant destination of those leaving Somalia. This section shall also focus on Kenyan policy in response to the evolving refugee situation. Finally, this paper will focus on the changing policy of Kenya, the attempts to resettle Somali refugees and to close the Dadaab complex. One will pose the question why this policy is not working.